The Role of Islamic Religious Education in Promoting Religious Moderation among Generation Z at MTsN 2 Bungo - Usamah Zulfiyatunnuha; Joni Juli Yandra; Siti Khamim; Baili Baili; Ulfa Adilla (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Generation Z faces challenges arising from ideological polarization, digital disruption, and identity fragmentation that threaten social cohesion. In this context, strengthening religious moderation has become a strategic necessity for safeguarding the nation’s ideological resilience. This study aims to analyze the role of Islamic Religious Education (IRE) in fostering religious moderation among Generation Z students at MTsN 2 Bungo, Bungo Regency, Jambi. The research employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and document analysis of curricula and instructional modules. The participants included Islamic Religious Education teachers, students from Grades VII–IX, and the madrasah principal, who were selected purposively. The findings indicate that Islamic Religious Education serves as an agent for the internalization of moderation values through three main dimensions: (1) the integration of the concept of wasathiyyah (Islamic moderation) into instructional materials and the Pancasila Student Profile Strengthening Project; (2) the implementation of dialogic learning practices that cultivate empathy, active tolerance, and ethical discussion skills; and (3) the enhancement of digital-religious literacy to counter radical narratives in cyberspace. The results suggest that the effectiveness of Islamic Religious Education lies not merely in the transmission of normative knowledge but also in the formation of a contextual, critical, and inclusive religious habitus. The study recommends strengthening the pedagogical competencies of Islamic Religious Education teachers within the framework of religious moderation, developing attitude assessment instruments integrated with digital learning ecosystems, and promoting policy synergy among the Ministry of Religious Affairs, schools, and media literacy communities. Practically, the findings emphasize the need to transform Islamic Religious Education from a doctrinal approach into a participatory learning model that is responsive to the characteristics of Generation Z.